1991
DOI: 10.1128/jb.173.19.6074-6087.1991
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and genetic analysis of a 13.1-kilobase-pair Pseudomonas denitrificans DNA fragment containing five cob genes and identification of structural genes encoding Cob(I)alamin adenosyltransferase, cobyric acid synthase, and bifunctional cobinamide kinase-cobinamide phosphate guanylyltransferase

Abstract: A 13.1-kb DNA fragment carrying Pseudomonas denitrificans cob genes has been sequenced. The nucleotide sequence and genetic analysis revealed that this fragment contained five different cob genes named cobN to cobQ and cobW. Based on the similarity of NH2-terminal sequences and molecular weights of the purified Cob proteins, CobQ was identified as cobyric acid synthase, CobP was identified as a bifunctional enzyme exhibiting both cobinamide kinase and cobinamide phosphate guanylyltransferase activities, and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 48 publications
(64 reference statements)
4
89
0
1
Order By: Relevance
“…2 (27). The sequence of these genes is homologous with that of genes of Pseudomonas denitrificans that have been shown to encode enzymes catalyzing reactions involved in joining adenosyl-CBI and DMB (2,4,5,9). These sequences and their analysis will be presented in detail elsewhere (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (27). The sequence of these genes is homologous with that of genes of Pseudomonas denitrificans that have been shown to encode enzymes catalyzing reactions involved in joining adenosyl-CBI and DMB (2,4,5,9). These sequences and their analysis will be presented in detail elsewhere (11).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies indicate that the CobII region is composed of four complementation groups. Correlation of the genetic map with available DNA sequence data for the CobI and CobIII regions of the operon suggests that three open reading frames are included in the CobIII region (5,(7)(8)(9)11).…”
mentioning
confidence: 99%
“…These studies suggested that the insertion of the adenosyl group takes place at the stage of cobyrinic acid a,c-diamide. In addition, cobO mutants G632 and G633 (7,8) have been shown to accumulate cobyrinic acid a,c-diamide specifically (28 and 4% of the amount of cobalamin produced by the parent strain, respectively), and the present study has revealed the enzymatic activity and substrate specificity of the cobO gene product. We infer from these data that the main physiological function of CobO is to adenosylate cob(I) yrinic a,c-diamide.…”
mentioning
confidence: 92%
“…An elevated adenosyltransferase activity (about 3 to 6 U mg of protein-' versus 0.1-0.3 U mg-1) was detected in SC510 Rif' strains containing plasmid pXL227, which carries the cobO gene (8). SC510 Rif(pXL227) was used as the source of the enzyme for purification.…”
mentioning
confidence: 99%
“…CHL H also exhibits 65% identity with ChlH, a putative Mg chelatase subunit from Synechocystis PCC 6803 (Jensen et al, 1996a). Hudson et al (1993) noted the strong similarity between the OLI protein and CobN, which is a subunit of the cobaltochelatase enzyme from Pseudomonas dentrificans (Crouzet et al, 1991). Similarly, the Arabidopsis CHL H protein shows 27% identity with CobN.…”
Section: Sequence Analysismentioning
confidence: 99%